Effectiveness of Saccharomyces boulardii CNCM I-745 in Adult Indian Patients with Diarrhoea: A Real-world, Multicentre, Retrospective, Comparative Study - Bhaskar Bikash Pal; Rupali Vinodchandra Bandagi; Kranthi Kiran Pebbili; Rahul Rathod; Bhavesh Kotak; Gauri Dhanaki; Snehal Shah (Adis, Springer Healthcare, 2024)
Abstract Background Multiple clinical studies have described the benefits of probiotic Saccharomyces boulardii (S. boulardii) CNCM I-745 against diarrhoea, but the real-world evidence supporting its use is lacking. Objective To evaluate effectiveness of the S. boulardii CNCM I-745 group in a real-world setting. Methods This was an electronic medical record (EMR)-based, retrospective, multicentre, comparative study in Indian adult patients presenting with diarrhoea managed between January 2020 and January 2022. Data of patients at the baseline visit, with a follow-up visit within 15 days, and who were administered S. boulardii CNCM I-745 (for the test group) or any other treatment modality excluding probiotics (for the control group) were considered. Effectiveness was evaluated on the basis of number of patients who did not complain of diarrhoea at follow-up. Results Of 30,385 adult patients with diarrhoea, 270 patients prescribed S. boulardii CNCM I-745 were included, while the control group comprised 1457 patients. The baseline median age of the test group was 47 years (range 19-86 years), while it was 44 years (range 19-100 years) for the control group. The majority of patients in both study groups were females (56.7% in the test and 51.5% in the control group). Median duration between visits was 5 days (range 1-15 days) in both study groups. In all, 77.8% patients (95% CI 72.34-82.59) in the test group did not complain of diarrhoea at follow-up, while the proportion was 15.8% (95% CI 13.95-17.76) in the control group (p < 0.05). Odds ratio (OR) for absence of diarrhoea in the S. boulardii CNCM I-745 group versus the control group was 18.7 (95% CI 13.6-25.7, p < 0.05). For subgroups on concomitant antibiotics, a significant advantage was noted again for the test versus the control group (76.8% versus 18.4%; p < 0.05; OR: 14.7 with 95% CI 8.8-24.4; p < 0.05). Conclusion The effect of S. boulardii CNCM I-745 probiotic in controlling diarrhoea was better than anti-diarrhoeal and/or oral rehydration therapy in real-world clinical practice. The effect was similar even with concomitant antibiotic usage.